Successful Treatment of Chronic Staphylococcus aureus-Related Dermatoses with the Topical Endolysin Staphefekt SA.100: A Report of 3 Cases - Joan E.E. Totté; Martijn B. van Doorn; Suzanne G.M.A. Pasmans (Case Reports in Dermatology, 2017)
Staphylococcus aureus plays an important role in skin and soft tissue infections and contributes to the pathophysiology of complex skin disorders such as atopic dermatitis. Bacterial resistance against commonly used antibiotics has increased considerably in the last decades demanding alternative treatment approaches. We present 3 cases where patients with chronic and recurrent S. aureus-related dermatoses were successfully treated with Staphefekt SA.100. Staphefekt SA.100 is a recombinant phage endolysin for topical skin application that specifically targets both methicillin-sensitive and methicillin-resistant S. aureus. As a consequence of its specific mechanism of action, bacterial resistance is unlikely to develop. In our 3 cases, resistance induction was not observed. Our results indicate that targeted treatment with Staphefekt might be an attractive alternative for (long-term) classical antibiotic therapy, and confirmatory randomized controlled trials are warranted to evaluate its clinical efficacy and safety.